Pengaruh Likuiditas dan Laverage Terhadap Probabilitas pada PT. Akasha Wira Internasional Tbk Tahun 2016-2023 - Andi Ariyanto; Eko Widodo; Trisnia Widuri (Universitas 45 Surabaya, 2025)
This study aims to determine the simultaneous and partial effect of Liquidity and Leverage on Probability. This type of research uses quantitative research because it leads to measurement methods and samples to test variables and hypotheses. The population in this study were all financial reports published on the company's official website for the period 2016-2023. The sample of this study was taken based on purposive sampling technique. In this study, the sample of the study was 32 financial reports. Data analysis used multiple linear regression. The results of the study showed that partially Leverage and Liquidity had a positive and significant effect of 0.000 <0.05 on Probability. Simultaneously Leverage and Liquidity had a positive and significant effect with an F value of 0.000 <0.05 on Probability at PT Akasha Wira International Tbk in 2016-2023. With a simultaneous determination coefficient of 60.4%. This study implies that the Leverage and Liquidity value factors greatly influence the Probability value.